Dynamic failure processes and failure mechanism of soil slope under random earthquake ground motions. Issue 133 (June 2020) - Zhao, Liuyuan; Huang, Yu; Chen, Zhiyi; Ye, Bin; Liu, Fang
Abstract: Understanding the failure processes and failure mechanism of slopes is essential in the seismic design of slopes. However, the effect of ground motion uncertainty on slope failure is unclear (for example, whether the slope failure processes differ under different ground motions). This study investigated the failure processes and failure mechanism of a soil slope subjected to random earthquake ground motions. Non-stationary random earthquake ground motions were generated based on the improved orthogonal expansion method and dynamic problems were solved using the FLAC3D software. We attempted to determine the slope sliding surface by analyzing the dynamic strain time history of monitoring points. Statistical results obtained using the probability density evolution method revealed that the slip surface extended from the toe to the crest of the slope during the earthquakes and that only one slip surface could be determined under an earthquake scenario. Additionally, the slip surface, time of failure, and failure duration differed under different earthquakes. The strain development patterns also differed and four typical failure modes were identified based on these patterns. The slope risk was assessed based on the sliding mass uncertainty. The proposed framework can be useful in evaluating slope failure processes and for seismic design in the field of slope engineering. Highlights: A high-efficiency analysis method was used for random seismic problems of slopes. Slope failure processes and mechanism under random earthquakes were investigated. Risk was assessed based on the failure surfaces and uncertainty of sliding mass.